Soil degradation and restoration in Africa - Lal, R.; Stewart, B. A. 1932- (Advances in soil science, 2019)
Soil degradation is a widespread problem in Africa resulting in low agricultural productivity while demand for food continues to increase. Degradation is caused by accelerated erosion, acidification, contamination, depletion of soil organic matter and plant nutrients, and salinization. Food and nutritional security of the growing population of Africa can only be achieved if degraded soils are restored, and soils of agroecosystems are managed prudently and sustainably. This book describes the soils of Africa, processes of soil degradation, extent and severity of soil degradation, and the impacts of degradation processes on food and nutritional security